THE EFFECTIVITY OF ONLINE LEARNING IN EXPLORING MATHEMATICAL ABILITY OF ELEMENTARY STUDENTS ASSISTED WHATSAPP GROUP APPLICATION - Dian Nurawaliah Sonjaya; Disman Disman (Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Mathematical exploration ability is very needed for student. This research focuses to looking for the effectivity of online learning activities in mathematics exploration ability of student in several Indonesia elementary school during the pandemic of covid-19 with the assistance of whatsapp group applications. Whatsapp group is used for connecting learning activities between teacher and student guardians or parents, between teacher and students, among students and among student guardians or parents during the covid-19 pandemic. This Research uses quantitative method. The technique of data collection using questionnaire with the assistance of google form applications. There are 119 respondents who contains 80 female student guardian and 39 male student guardians. Based of collection data which have been done 86,5% respondents answer that learning with assistance of whatsapp group runs effectivitily for exploring mathematical ability. 92,25% respondents answer that teacher always helping online learning by whatsapp group during The covid-19 pandemic. Using Whatsapp group will continue to be used until the better application is found. Abstrak Kemampuan eksplorasi matematis sangat dibutuhkan siswa. Penelitian ini difokuskan untuk mencari efektivitas kegiatan pembelajaran online dalam kemampuan eksplorasi matematika siswa di beberapa sekolah dasar Indonesia pada saat pandemi covid-19 dengan bantuan aplikasi whatsapp group. Grup Whatsapp digunakan untuk menghubungkan kegiatan pembelajaran antara guru dengan wali siswa atau orang tua, antara guru dan siswa, antar siswa dan antar wali siswa atau orang tua selama pandemi covid-19. Penelitian ini menggunakan metode kuantitatif. Teknik pengumpulan data menggunakan kuisioner dengan bantuan aplikasi google form. Ada 119 responden yang terdiri dari 80 wali murid perempuan dan 39 wali murid laki-laki. Berdasarkan pengumpulan data yang telah dilakukan 86,5% responden menjawab bahwa pembelajaran dengan bantuan kelompok whatsapp berjalan efektif untuk menggali kemampuan matematika. 92,25% responden menjawab bahwa guru selalu membantu pembelajaran online oleh kelompok whatsapp selama pandemi covid-19. Menggunakan grup Whatsapp akan terus digunakan hingga ditemukan aplikasi yang lebih baik. Kata Kunci : Kemampuan Eksplorasi Matematis, Pembelajaran Online, Siswa Sekolah Dasar